2013
DOI: 10.1016/j.vaccine.2013.04.032
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella Typhimurium lacking the Znuabc transporter is attenuated and immunogenic in pigs

Abstract: Meat contamination by Salmonella spp is emerging as a major cause of human enteric infections in industrialized countries. The attempts to reduce human cases of salmonellosis encompass pre- and post harvest interventions. In this context, vaccination of pigs may represent an effective instrument in eliminating/reducing Salmonella burden through the food chain. We have previously demonstrated that Salmonella Typhimurium lacking the ZnuABC transporter (S. Typhimurium ΔznuABC) is a promising candidate live vaccin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 28 publications
2
22
0
Order By: Relevance
“…In previous studies, we showed that S. Typhimurium lacking the ZnuABC transporter is an effective oral vaccine in preventing disease and in reducing colonization of gut and systemic organs of pigs experimentally challenged with virulent Salmonella microorganisms [19,20]. The results presented herein, corroborate and extend these findings, and also show that pigs intramuscularly vaccinated with S. Typhimurium znuABC exhibit a degree of protection against virulent S. Typhimurium infection comparable to that observed in orally vaccinated animals.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…In previous studies, we showed that S. Typhimurium lacking the ZnuABC transporter is an effective oral vaccine in preventing disease and in reducing colonization of gut and systemic organs of pigs experimentally challenged with virulent Salmonella microorganisms [19,20]. The results presented herein, corroborate and extend these findings, and also show that pigs intramuscularly vaccinated with S. Typhimurium znuABC exhibit a degree of protection against virulent S. Typhimurium infection comparable to that observed in orally vaccinated animals.…”
Section: Discussionsupporting
confidence: 85%
“…Typhimurium ATCC14028 and its isogenic mutant strain denominated S. Typhimurium znuABC were used in this study. Attenuated strain (S. Typhimurium znuABC) was produced according to the method previously described [17][18][19]. Wild type and mutant strains were cultured at 37 • C in Brain Heart Infusion (Oxoid Ltd., Basingstoke, UK), harvested by centrifugation and then washed twice in ice-cold Phosphate Buffer Solution (PBS) (Sigma-Aldrich, Milan, Italy).…”
Section: Salmonella Spp Culturesmentioning
confidence: 99%
See 3 more Smart Citations